PENGARUH METODE PEMBELAJARAN DAN TINGKAT KREATIVITASTERHADAP HASIL BELAJAR IPA - WONDAL, ROSITA (JURNAL PENDIDIKAN ANAK USIA DINI, 2011)
The objective of this research is to find out whether there is any effect of instructional method and level of creativity on science learn result of grade three Elementary Student at Tomalima-Passo Ambon. This research was conducted in grade three Elementary Student at Tomalima-Paso Ambon during 2011 academic year. The first result of the research describes that the level of science learn result using the demonstration-experiment (De-eks) instructional method is higher than using discussion-speech (Dis-ce) instructional method. Second, There is a significant difference between a group with high level creativity by using the demonstration-experiment (De-eks) instructional method and a group with high level creativity by using discussion-speech (Dis-ce) instructional method. Third, there is a difference in science learn result between a group with low level creativity by using the demonstration-experiment (De-eks) instructional method and a group with low level creativity by using discussion-speech (Dis-ce) instructional method. Fourth, There is no significant difference interaction between instructional method and level of creativity to science learn result.Keywords: instructional method, level of creativity and science learn result